Synthesis of vanillin dareivatives as anti-cancer (cervical cancer) using pharmacophore modelling and invitro brine shrimp assay as prelimanary identification of cytotoxic properties - Nur Syairah, Binti Dagang (Universiti Malaysia Sarawak, UNIMAS, 2012)
Cancer disease is the result of uncontrolled cell growth. The process by which a normal cell changes into one that behaves abnormally can take a long time and is often triggered by outside influences. Cervical cancer is a disease that affects the cervix in the female reproductive system. The cervix is the lower portion of the uterus that connects the upper vagina to the uterus. For this research, the targeted drugs are created to block the growth and spread of the cell cancer by preventing or cure the cancer cells from dividing and destroying the cells. Anti-cancer cervical agent was synthesized using vanillin derivatives via Schiff base condensation reaction. The proposed compounds was characterized using GCMS, NMR, FTIR, TLC and CHN analysis. To validate these compounds, cytotoxicity testing using brine shrimp (Artemia salina) was be performed. Computer Aided Drug Design (CADD) through pharmacophore modelling was attempted by a 3-D pharmacophore model that was developed using Ligand Scout 3.03 program/software, with the training set comprising of six established cervical cancer drugs (training set) from published literature and database. The best pharmacophore hypothesis was generated consisting of hydrogen bond acceptor (HBA), hydrogen bond donor (HBD) and negative ionizable (NI). The best generated pharmacophore model validated the twenty synthesized vanillin derivatives (test set). All vanillin derivatives were mapped to the hypothesis and predicted compounds to mimic anti-cancer agent. The best vanillin derivatives that have the best mapping and highest score for fitting as will be suitable to be considered for design the new anti cancer agents and further investigation should be performed. In this study, N-[(Z)-(4-hydroxy-3-methoxy-phenyl)methyleneamino]furan-2- carboxamide and 2-methoxy-4-[(Z)-phenyliminomethyl]phenol that are the best compound for anti cancer agent (cervical) cancer based on the result of pharmacophore modelling software and also based on biological activity.